2017
DOI: 10.1180/claymin.2017.052.4.08
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between measured plastic limit and plastic limit estimated from undrained shear strength, water content ratio and liquidity index

Abstract: The detection of the plastic limit of clays is subject to human error. Several attempts have been made to correlate across studies the geotechnical properties of fine-grained soils (water content, liquidity index, shear strength, etc.). Based on the premise that the liquidity index and water content ratio can be correlated directly, an alternative method to obtain indirectly the plastic limit is suggested here. The present study investigated 40 natural clayey samples of various mineralogies and origins and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…It is found that the change in plasticity index in terms of LL and h can be obtained by Equation (14) and shown by Figure 18. 0.9062 for common analysis.…”
Section: Pimentioning
confidence: 95%
See 2 more Smart Citations
“…It is found that the change in plasticity index in terms of LL and h can be obtained by Equation (14) and shown by Figure 18. 0.9062 for common analysis.…”
Section: Pimentioning
confidence: 95%
“…Comparisons with actual experimental dataset forms the first way of the confirmation process. In addition, PI = −9.7 + 0.015h + 0.74LL ( 14) The R 2 value of the most fitting equation is obtained as the discussion with the literature sources creates the second way. The first step of the confirmation process has been studied and explained before, together with the studies of the acquirement of the equation.…”
Section: Pimentioning
confidence: 99%
See 1 more Smart Citation
“…The yield stress is a measure of the gel strength or the strength of the microstructure forming the gel. This should be related to the plastic limit used to characterize the rheological properties of clay suspensions (Spagnoli & Feinendegen, 2017). The ageing behaviour characterizing the structural recovery behaviour in terms of yield stress vs. ageing time was also characterized.…”
Section: Methodsmentioning
confidence: 99%
“…While Casagrande suggested an average (Cu) of 2.65 kN/m 2 considering the spread of the values depending of the apparatus of determination of LL, other authorities on the subject had proposed a range between 0.7 kN/m 2 and 2.8 kN/m 2 and suggested the use of the Casagrande apparatus for determining LL ( Sharma and Bora, 2003 ). It was remarked that the failure of undrained clay is self-weight-induced and the use of in-situ experimental setups to validate constitutive relations becomes difficult due to the impact of the weight of cone on the failure of clay ( Spagnoli and Feinendegen, 2017 ). Note, mechanical properties (Es, υ) of clay have been used in the previous studies as well as hydro-mechanical properties (LL, PL, and WC).…”
Section: Introductionmentioning
confidence: 99%